Plagues in Our Criminal Justice System: An Analysis of Wrongful Conviction in Canada and other Countries - Taylor-Baer, Charlotte M.; Anderson, Gail S. (The Wrongful Conviction Law Review, 2023)
This study compared the causes of wrongful convictions in Canada, the United States, the United Kingdom, Australia, and New Zealand to a) determine the main causes of wrongful convictions in different countries, b) determine if the cause(s) of wrongful convictions significantly differ between each country, c) determine what, if any, recommendations arose from these cases, and d) if any of these recommendations could be implemented in a Canadian setting. The main causes were witness perjury, forensic error, and procedural error (Canada), witness perjury (US), witness perjury and police misconduct (UK), police misconduct (Australia), and procedural error (New Zealand). Kruskal-Wallis tests indicated significant differences in distribution between these countries for medicolegal death investigations, bitemark analysis, procedural error, police misconduct, inadequate legal defence, eyewitness misidentification, and witness perjury. Objectives c and d were addressed through a content analysis resulting in the following five themes emerging: lack of accountability, education, accessibility, discrimination, and post exoneration.